Fiscal Rules, Bailouts, and Reputation in Federal Governments - Dovis, Alessandro; Kirpalani, Rishabh (American Economic Review, 2020)
Expectations of transfers by central governments incentivize overborrowing by local governments. In this paper, we ask if fiscal rules can reduce overborrowing if central governments cannot commit to enforce penalties when rules are violated. We study a model in which the central government’s type is unknown and show that fiscal rules increase overborrowing if the central government’s reputation is low. In contrast, fiscal rules are effective in lowering debt if the central government’s reputation is high. Even when the central government’s reputation is low, binding fiscal rules will arise in the equilibrium of a signaling game. (JEL E62, H62, H63, H77, H81)